1996
DOI: 10.1111/1523-1747.ep12363389
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Fibroblast Cell Growth, Matrix Production, and Granulation Tissue Formation by Connective Tissue Growth Factor

Abstract: Connective tissue growth factor (CTGF) is a 36-to 38-kDa peptide that is selectively induced by transforming growth factor-beta (TGF-beta) in fibroblastic cell types. We compared the biologic activities of CTGF with TGF-beta on fibroblasts in culture and in animal models of fibroplasia. CTGF was active as a mitogen in monolayer cultures of normal rat kidney fibroblasts. CTGF did not stimulate anchorage-independent growth of NRK fibroblasts, however, or inhibit the growth of mink lung epithelial cells, distingu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
607
4
9

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 696 publications
(647 citation statements)
references
References 36 publications
26
607
4
9
Order By: Relevance
“…The TGF‐β‐CTGF pathway activated cells with a fibrogenetic phenotype and initiated cellular processes underlying fibrosis 30, 31. Connective tissue growth factor has also been involved in the induction of cardiac fibrosis in animal models of LV remodelling 32, 33. In our study, we observed that overexpression of miR‐503 increased the expression of TGF‐β and CTGF in CFs, an effect that was abolished by the co‐application of Apelin‐13.…”
Section: Discussionsupporting
confidence: 53%
“…The TGF‐β‐CTGF pathway activated cells with a fibrogenetic phenotype and initiated cellular processes underlying fibrosis 30, 31. Connective tissue growth factor has also been involved in the induction of cardiac fibrosis in animal models of LV remodelling 32, 33. In our study, we observed that overexpression of miR‐503 increased the expression of TGF‐β and CTGF in CFs, an effect that was abolished by the co‐application of Apelin‐13.…”
Section: Discussionsupporting
confidence: 53%
“…Early studies described the functions of CTGF as connective tissue cell proliferation, differentiation, chemotaxis and adhesion [8,9,43]. CTGF is synthesised by fibroblasts and stimulates the proliferation and chemotaxis of these cells as well as the production of various ECM components in fibroblast cultures, including collagen I, fibronectin and collagen IV [44,45]. CTGF is produced at increased levels during normal wound repair [8] and at sites of fibrogenesis [11,45].…”
Section: Discussionmentioning
confidence: 99%
“…Only treatment with TGFb was accompanied by a parallel induction of collagen I transcription, whereas the early transient increase of CTGF induced by EGF/TGFa did not alter collagen I transcription. It has been speculated that CTGF is a downstream mediator of TGFb actions on the ECM, on the proliferation of ®broblasts and the development of ®brosis (Grotendorst, 1997;Frazier et al, 1996;Grotendorst et al, 1996). This is of paramount importance for the pathogenesis of pancreatic diseases as e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In this context Grotendorst and colleagues recently identi®ed a new TGFb responsive element located in the CTGF-promoter . Recombinant CTGF has recently been shown to stimulate type I collagen and ®bronectin production in NRK ®broblasts (Frazier et al, 1996). CTGF could thus be a downstream e ector of TGFb which is a potent stimulator of extracellular matrix production.…”
Section: Introductionmentioning
confidence: 99%